PENGARUH SERVANT LEADERSHIP TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN BAGIAN SERVICE CUSTOMER PT. MATAHARI DEPARTEMEN STORE TBK SAMARINDA - Devianita, Nur Illiyin (MOTIVASI, 2020)
This study aims to determine the measure of servant leadership on organizational citizenship behavior. The research sample of 73 employees of PT. Matahari Department Store Tbk Samarinda. This sampling technique uses proportionate stratified random sampling technique. Research data were collected using two types of questionnaires that measure servant leadership and organizational citizenship behavior among employees. Data analysis techniques using simple linear regression with the help of SPSS 23 for windows statistical program. The results showed that there was a significant correlation between servant leadership and organizational citizenship behavior with an RÂ² value of 0.496 with a significance level of 0,000 (p <0.01) which means that the variation of organizational citizenship behavior is influenced by the servant leadership variable of 49.6%.